(untitled) (Research, Society and Development, 2020)
In the face of maxillary atrophy, the sinus floor tends to exhibit only a thin cortical bone wall, imposing limitations on the placement of dental implants. The purpose of this literature review was to evaluate the scientific performance on the importance of lifting the maxillary sinus for the installation of dental implants. A literature review was conducted using the PubMed/Medline, Scielo and Science direct databases. Articles published between 2014 and 2020 were selected based on the following inclusion criteria: Availability of the full text, publication in English and clarity on the methodological details used. Studies have shown that the anatomy of the maxillary sinus must be investigated before planning the implants in the posterior region of the maxilla, in order to diagnose the presence of sinus pathologies, the presence of septa and pneumatization. It is important to note that the lifting of the maxillary sinus is a procedure that has good results, showing few complications in the postoperative period. In addition, cone beam computed tomography should be the imaging exam of first choice when this procedure is indicated for the installation of dental implants.